Separation of Isomeric O-Glycans by Ion Mobility and Liquid Chromatography–Mass Spectrometry - Jin, Chunsheng; Harvey, David J; Struwe, Weston B; Karlsson, Niclas G (Analytical chemistry (Washington), 2019)
Glycosylation is one of the most important post-translational modifications essential for modulating biological functions on cellular surfaces and within cells. Glycan structures are not predictable from the genome since their biosynthesis is nontemplate driven and subject to multiple sequential and competitive glycosyltransferases/glycosidases. From a structural viewpoint, their analysis presents a particular challenge in terms of sensitivity and structural characterization. Porous graphitized carbon liquid chromatography coupled mass spectrometry (PGCLC-MS) is arguably the gold-standard for the structural characterization of glycoconjugates, especially complex mixtures typical in biological samples. This high performance is due in large part to chromatographic separation of isomers and the information delivered by collision induced fragmentation of each glycan in the mass spectrometer. More recently, ion mobility mass spectrometry (IM-MS) has emerged as an effective tool for gas-phase separation of isomeric oligosaccharides that has been demonstrated with small oligosaccharides and N-glycans. Here, we present a direct comparison of the IM- and LC-separation of O-glycans from porcine gastric and human salivary mucins. Our results identify structures, which are resolved by PGCLC and/or IM, validating the combination of the two methods. Taken together, the incorporation of both techniques into a single platform would be powerful and undoubtedly valuable for determining the full glycome of unknown samples.